INTEGRATION TRADFI AND DEFI: A NEW FINANCIAL MODEL FOR UZBEKISTAN (Western European Journal of Historical Events and Social Science, 2026)
This article explores the prospects of integrating centralized banking systems (TradFi) with decentralized finance (DeFi) in the context of Uzbekistan’s evolving financial ecosystem. It highlights the advantages of traditional finance, such as stability and regulation, alongside the technological benefits of DeFi, including automation and transparency. The study identifies key risks and legal gaps in the current regulatory framework and analyzes international approaches. Based on this, a controlled, permissioned integration model is proposed, combining open banking, tokenization, and gradual CBDC adoption. The article concludes that a balanced approach can support financial innovation while ensuring system stability. Special attention is given to the legal and regulatory environment of Uzbekistan, where existing legislation creates structural gaps in integrating crypto-assets into the national financial system. The article proposes a hybrid financial model based on open banking, tokenization of assets, permissioned DeFi platforms, and gradual integration with central bank digital currency infrastructure.